2016
DOI: 10.1016/j.apmr.2015.11.018
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory Training Improves Blood Pressure Regulation in Individuals With Chronic Spinal Cord Injury

Abstract: Objective To investigate the effects of resistive Respiratory Motor Training (RMT) on pulmonary function and orthostatic stress-mediated cardiovascular and autonomic responses in individuals with chronic Spinal Cord Injury (SCI). Design Before-after intervention case-controlled clinical study. Setting Participants Individuals with chronic C3-T2 SCI diagnosed with orthostatic hypotension (OH) (n=11) and healthy, non-injured (NI) controls (n=10). Intervention 21 ± 2 (mean ± SD) sessions of resistive insp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
2
3

Year Published

2017
2017
2019
2019

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 67 publications
(59 reference statements)
0
25
2
3
Order By: Relevance
“…There was no effect of RMT on lung volumes (except a lower FRC at follow‐up), which is in disagreement with the only two previous studies investigating the effect of combined RMT on lung function, both of which reported improved FVC (Aslan et al . ; Legg Ditterline et al . ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There was no effect of RMT on lung volumes (except a lower FRC at follow‐up), which is in disagreement with the only two previous studies investigating the effect of combined RMT on lung function, both of which reported improved FVC (Aslan et al . ; Legg Ditterline et al . ).…”
Section: Discussionmentioning
confidence: 99%
“…Although studies of RMT in individuals with SCI of all levels and completeness have reported improved forced VC (FVC) and blood pressure (BP) regulation (Aslan et al . ; Legg Ditterline et al . ), the effects of RMT on exercise performance and cardiopulmonary function have not been examined.…”
Section: Introductionmentioning
confidence: 99%
“…(27). Moreover, Aslan et al proved that resistive respiratory muscle training for one month significantly improved blood pressure regulation and pulmonary function (FVC and FEV1) in patients with C3-T2 chronic spinal cord lesion (14). Finally, Berlowitz and Tamplin in their meta-analysis study, which included 11 studies on patients with cervical spinal cord injury, stated that Respiratory muscle training significantly improved vital capacity, maximal inspiratory pressure and maximal expiratory pressure (16).…”
Section: Discussionmentioning
confidence: 99%
“…The total management of patients requires a holistic, multidisciplinary approach to ensure effective rehabilitation, which depends upon awareness of the risks, and a thorough understanding of the pathophysiology of mucus plugging atelectasis and the alterations in pulmonary mechanics (14). However, the leading causes of morbidity and mortality in spinal cord injury population are airway mucus plugging and atelectasis (15).…”
Section: Introductionmentioning
confidence: 99%
“…The objective of the reported study was to investigate if our original reciprocal respiratory training approach, already reported to be effective in improving blood pressure regulation in individuals with SCI-induced orthostatic hypotension 2 , can affect baroreflex function which is often deconditioned in the general SCI population. Study groups intentionally included participants with different levels and severity of injury with a variety of respiratory-cardiovascular functional states.…”
Section: Dear Dr Chanmentioning
confidence: 99%